High-Resolution Local Gravity Field Determination at the Sub-Millimeter Level using a Digital Zenith Camera System - Hirt, Christian; Seeber, G. (Springer, 2005)
During the last years the observation of vertical deflections experienced a revival due to the development of state-of-the-art Digital Zenith Camera Systems in Zurich and Hanover. Other than analogue instruments of geodetic astronomy, the new digital observation Systems provide vertical deflection data very fast and highly-accurate. One main application for these instruments is the precise gravity field determination in local areas applying the classical method of astronomical leveling. This paper presents preliminary results of an ongoing local gravity field survey carried out in a test area near Hannover in Northern Germany. Here, a subterranean salt deposit influences the fine structure of the gravity field. At the Earth's surface a profile was established with densely arranged stations (50 m spacing). At 131 stations high-precision vertical deflection data has been collected using the Hanover Digital Zenith Camera System TZK2-D. Based on extensive instrumental calibration and the highly redundant data acquisition at each Station, an unprecedented accuracy level of about 0".08 is reached for the deflection data. The local equipotential profile is directly obtained through Integration of vertical deflections in the course of the profile. Error propagation shows that the variations of the local gravity field are determined at an accuracy level of 0.1 required for example in engineering projects (linear accelerators). As a conclusion the study demonstrates that Digital Zenith Cameras are ideal instruments for accessing the sub-millimeter accuracy domain for gravity field studies in local areas.